Currency Convertibility in the Economic Community of West African States - Nsouli, Saleh; McLenaghan, John.; Riechel, Klaus-Walter. (Washington, D.C. : International Monetary Fund, 1982)
One of the principal aims of the effort to integrate the economies of the 16 member countries of the Economic Community of West African States (ECOWAS) is to expand intra-Community trade. This objective is to be achieved partly through the elimination of quantitive and other restrictions on trade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet